Rancang Bangun Sistem Penerimaan Peserta Didik Baru Berbasis Web (Studi Kasus: SMA Rimba Madya) - Muhammad Firli Fadilah; Yono Cahyono (CV. Multi Kreasi Media, 2022)
Admission of new students is a form of process that exists in educational institution that functions to find the best prospective students who are selected according to the categories determined by the school to become their students. Admission of new students at Rimba Madya Senior High School still uses the conventional method, namely students come directly to the school to fill out forms, bring registration requirements and pay registration fees, then the admin manages that data manually and inputs them into Microsoft Excel one by one. This results in less efficient use of time and energy. To help rapidly the admission process for new students, a web-based application system with the PHP programming language and Mysql database is needed. By implementing a web-based admission of new students system at Rimba Madya Senior High School, it can overcome the weaknesses of the conventional new student registration system and help the committee and prospective new students in carrying out the admission process of new students at Rimba MADYA Senior High School easily and quickly.